Impact of Auxiliary Markings on Intersection Safety - Franata, Mhd Tommy; Siregar, Martha Leni; Kusuma, Andyka (Smart City, 2024)
The rapid growth of motorcycle vehicles coupled with inadequate traffic discipline contributes to an escalating rate of traffic accidents and casualties. This study investigates the efficacy of auxiliary road markings in enhancing traffic safety and intersection performance along Lieutenant Sutopo Street, Promoter Street, and Boulevard BSD East in South Tangerang, Indonesia. Employing the Traffic Conflict Technique (TCT), the research evaluates safety enhancements and service level alterations subsequent to the installation of road markings. Preliminary observations highlight significant safety concerns and traffic conflicts at the intersection. Consequently, auxiliary road markings are strategically installed to regulate driver behavior, enhance lane discipline, and improve visibility. Post-installation observations revealed a significant decrease in total vehicle conflicts, though the percentage of severe conflicts slightly increased. Initially rated as Level of Service (LOS) F with high delays, the LOS remained the same post-marking installation but with reduced delays. Further cycle time adjustments improved the LOS to E, indicating a substantial overall reduction in delays. The findings suggest that although auxiliary road markings effectively reduce traffic conflicts and improve intersection performance, additional measures are necessary to address the severity of these conflicts. The study offers valuable insights into the effectiveness of road safety interventions, supporting broader strategies for improving traffic management and safety in urban areas.